HADITH ON WEALTH DISTRIBUTION AND BUSINESS ETHICS: A Bibliometric Analysis of Global Research Trends (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
The research paper is a bibliometric mapping of the world's research on hadith and wealth allocation and the ethics of Islamic business. Using VOSviewer software, the analysis based on the 158 articles indexed by Scopus in the period of 2008-2025 was used to determine the growth of publications, networks of collaboration, institution performance, and development of themes. The findings show that there were six times more publications at the time of study, with Malaysia, Indonesia, and the United States becoming the major contributors. Some of the major institutions, like the Eberly College of Business and Information Technology, Kent Business School, and the International Centre of Education in Islamic Finance, are strategic in promoting this subject. According to keyword mapping, there are five key thematic clusters, which lay stress on a transition between the institutional and financial focus and the philanthropic ones, namely waqf, zakat, and redistribution of wealth. The research provides an immense gap in the literature since it represents the first bibliometric mapping of the scholarship on hadith in both economic and ethical aspects, thus contributing to the theoretical formulation of Islamic economics and giving direction to future cross-disciplinary work.[Makalah penelitian ini merupakan pemetaan bibliometrik atas penelitian global mengenai hadis, alokasi kekayaan, dan etika bisnis Islam. Dengan menggunakan perangkat lunak VOSviewer, analisis yang didasarkan pada 158 artikel yang terindeks oleh Scopus pada periode 2008-2025 digunakan untuk menentukan pertumbuhan publikasi, jaringan kolaborasi, kinerja institusi, dan perkembangan tema. Hasil penelitian menunjukkan bahwa jumlah publikasi meningkat enam kali lipat pada saat penelitian, dengan Malaysia, Indonesia, dan Amerika Serikat menjadi kontributor utama. Beberapa institusi utama, seperti Eberly College of Business and Information Technology, Kent Business School, dan International Centre of Education in Islamic Finance, berperan strategis dalam mempromosikan bidang ini. Berdasarkan pemetaan kata kunci, terdapat lima kluster tematik utama yang menekankan transisi antara fokus institusional dan keuangan dengan fokus filantropis, yaitu waqf, zakat, dan redistribusi kekayaan. Penelitian ini mengisi celah besar dalam literatur karena mewakili pemetaan bibliometrik pertama tentang studi hadis dalam aspek ekonomi dan etika, sehingga berkontribusi pada formulasi teoretis ekonomi Islam dan memberikan arah bagi kerja lintas disiplin di masa depan.]